Surface engineering for biological recognition - Yeh, Yun-Peng (Cranfield University, 2010)
The underlying idea of this thesis is that the surface chemical and morphological nature of bacterial strains uniquely differentiates one from another and hence can be used as the basis for their identification and control. It follows that their interactions with an artificial substratum uniquely characterize them. In principle, potentially it is easier and faster to evaluate the interfacial energy between a bacterium and a substratum than to characterize its genome or determine molecular biomarkers characteristic of the strain, hence validation of this thesis opens the way to rapid screening and diagnosis. Auxiliary to this main idea, an advanced metrology for evaluating the interfacial energies has been developed, exploiting the power of kinetic analysis.
Keywords: Identification; Interfacial energy; Kinetic analysis